Don't Point That Thing at Me : Charlie Mortdecai #1 - Bonfiglioli, Kyril (New York : The Overlook Press, 2015)
A wealthy art dealer's talent for attracting loose women and trouble leads him into conflict with the British secret service.
"The first Charlie Mortdecai novel"--Cover.
Keywords: Aristocracy (Social class) -- Fiction; Art dealers -- Fiction; Art thefts -- Fiction; Mortdecai, Charlie (Fictitious character) -- Fiction; Aristocracy -- Fiction; Art dealers -- Fiction; Art thefts -- Fiction; Mortdecai, Charlie (Fictional character) -- Fiction; England -- Fiction; England -- Fiction; Mystery fiction; Humorous fiction